Analysis of the impact of local government debt policy on the financial ecological environment-based on debt level and debt structure perspectives - Wang, Zejun; Yan, Jiale; Xu, ShaoKang; Yi, Zhu; Huang, Yongjian; Zhang, Xuedong (Frontiers in Environmental Science, 2023)
This paper employs panel data from 227 prefecture-level cities in China spanning the period from 2000 to 2020 to investigate the effects and influences of local government debt policies on the financial ecological environment. Considering regional economic foundation, financial development, government governance, and the construction of the social credit system, our analysis reveals the following outcomes regarding debt level and debt structure: Firstly, we find that higher debt levels and an increased proportion of hidden debt at the local government level have impacts on various dimensions of the financial ecological environment. Specifically, debt expansion facilitates regional economic foundations and financial development but hampers government governance and the construction of the social credit system, leading to a deterioration in the development of the financial ecological environment. Furthermore, employing a threshold regression model, we have not identified a significant nonlinear relationship in this context. Secondly, local government debt exhibits a reverse spatial spillover effect on the financial ecological environment of surrounding regions, contrasting with the effects observed within the local area. This effect manifests as the enhancement of the financial ecological environment in neighboring areas.